Vaccination Decision-Making and HPV Knowledge: How Informed and Engaged Are Young Adult HPV Vaccine Recipients in Australia?. (2nd April 2014) - Laidsaar-Powell, Rebekah C.; McCaffery, Kirsten J.; Mather, Tanya; Juraskova, Ilona
Abstract : Objectives . To date, there has been limited research on the decision-making process of HPV vaccine recipients. This study aimed to explore HPV-related knowledge, vaccination decision-making, and post vaccination attitudes about sexual behaviour in women who participated in the Australian school- and population-based HPV vaccine program. Materials and Methods . 102 female university students who had received the HPV vaccine (<27 years) completed scales on knowledge, vaccination decision-making, and post vaccination sexual attitudes. Results . HPV-related knowledge was low (M = 57 %), and women felt moderately involved in the vaccination decision (M = 62 %). Most women had not changed their sexual attitudes as a consequence of vaccination; however, some reported that since vaccination they feel less concerned about sexual health (19%). There were no significant differences between school- and population-based recipients on HPV knowledge (P = . 559 ) or post vaccination sexual attitudes (P = . 709 ). School-based recipients were significantly less autonomous in their decision-making (P = . 001 ). Conclusion . Poor knowledge indicates a need for provision of information about HPV and post vaccination sexual health. Additionally, policy makers and health professionals may benefit from reiterating the importance of continued sexual health practices to HPV vaccine recipients. Future research should assess whether young women need to be more involved in the informed decision-making process for HPV vaccination.